Global left atrial failure in heart failure - Triposkiadis, Filippos; Pieske, Burkert; Butler, Javed; Parissis, John; Giamouzis, Gregory; Skoularigis, John; Brutsaert, Dirk; Boudoulas, Harisios (European journal of heart failure, 2016)
The left atrium plays an important role in the maintenance of cardiovascular and neurohumoral homeostasis in heart failure. However, with progressive left ventricular dysfunction, left atrial (LA) dilation and mechanical failure develop, which frequently culminate in atrial fibrillation. Moreover, LA mechanical failure is accompanied by LA endocrine failure [deficient atrial natriuretic peptide (ANP) processing‐synthesis/development of ANP resistance) and LA regulatory failure (dominance of sympathetic nervous system excitatory mechanisms, excessive vasopressin release) contributing to neurohumoral overactivity, vasoconstriction, and volume overload (global LA failure). The purpose of the present review is to describe the characteristics and emphasize the clinical significance of global LA failure in patients with heart failure.